Final answer:
To solve the equation 11 - 12y = 3 + 6x for y, combine like terms and isolate y on one side of the equation.
Step-by-step explanation:
To solve the equation 11 - 12y = 3 + 6x for y, we need to isolate y on one side of the equation.
Step 1: Combine like terms by adding 12y to both sides of the equation.
11 - 12y + 12y = 3 + 6x + 12y
Simplifying, we get:
11 = 3 + 6x + 12y
Step 2: Combine the constant terms by subtracting 3 from both sides of the equation.
11 - 3 = 3 + 6x + 12y - 3
Simplifying, we get:
8 = 6x + 12y
Step 3: Solve for y by isolating the term with y on one side.
Subtract 6x from both sides:
8 - 6x = 6x + 12y - 6x
Simplifying, we get:
8 - 6x = 12y
Finally, divide both sides by 12:
y = (8 - 6x)/12